Molecular prevalence and genetic diversity analysis of Enterocytozoon bieneusi in humans in Hainan Province, China: High diversity and unique endemic genetic characteristics - Zhang, Tiemin; Ren, Guangxu; Zhou, Huanhuan; Qiang, Yu; Li, Jiaqi; Zhang, Yun; Li, Tingting; Zhou, Yunfei; Wang, Yuan; Lai, Xiuyi; Lei, Shen; Tan, Feng; et al. (Frontiers in Public Health, 2022)
Enterocytozoon bieneusi is a zoonotic pathogen commonly found in humans and animals all over the world. Here, we investigated the occurrence and genotype constitute of E. bieneusi among the individuals from Haikou city of Hainan, China. A total of 1,264 fecal samples of humans were collected, including 628 samples from patients with diarrhea (325 adults and 303 children) and 636 samples from the asymptomatic population (383 college students and 253 kindergarten children). E. bieneusi was detected using nested polymerase chain reaction (PCR) amplification of the internal transcribed spacer (ITS) region. A phylogenetic tree was constructed using a neighbor-joining tree construction method. The overall prevalence of E. bieneusi was 3.7% (47/1,264), while it was 5.6% in the patients with diarrhea (5.8% in adults and 5.3% in children) and 1.9% in the asymptomatic population (2.9% in college students and 0.4% in kindergarten children). The prevalence of E. bieneusi in humans with diarrhea was significantly higher than that in the asymptomatic population (χ2 = 36.9; P < 0.05). A total of 28 genotypes were identified, including ten known genotypes: CHG2 (n = 3), CHG3 (n = 5), CHG5 (n = 10), CM21 (n = 1), EbpA (n = 1), EbpC (n = 1), PigEBITS4 (n = 1), PigEBITS7 (n = 1), SHR1 (n = 4), Type IV (n = 2), and 18 novel genotypes (HNH-1 to HNH-18; one each). All these genotypes were categorized into three groups, including group 1 (n = 6), group 2 (n = 14), and group 13 (n = 8). This was the first study on the identification of E. bieneusi among humans in Hainan, China. The correlation between E. bieneusi infection and diarrhea was observed. The high diversity and distinctive distribution of E. bieneusi genotypes found in this study reflected the unique epidemic genetic characteristics of E. bieneusi in humans living in Hainan.